Foresight and One CGIAR - Arndt, Channing (2021)
Channing Arndt POLICY SEMINAR Socio-Technical Innovation Bundles for Agri-Food Systems Transformation: Implications for research and the One CGIAR agenda MAR 19, 2021 - 09:30 AM TO 11:00 AM EDT